Emerging Threat: Monkeypox Virus - Unraveling the Challenges and Preparedness - Anila Jaleel; Ghulam Farid; Hira Jaleel (ziauddin University, 2024)
Monkeypox is a DNA virus that belongs to the family of smallpox, with an incubation period of seven to 14 days and may last up to 21 days1. The Virus replicates on reaching the host cells, from where it spreads to lymph nodes and then to distant organs. The symptoms include fever, lymphadenopathy, and mucocutaneous lesions. The infection does not spread during the incubation period but may spread on being symptomatic to drying of scabs. Smallpox vaccination protects against monkeypox but its vaccination has been developed. An outbreak of pox appeared and spread rapidly across Europe, America, and then to all six continents2.